Аналіз алгоритмів youtube - Гриценко, І. О. (ХНУРЕ, 2024)
This work is devoted to analysis of the algorithms of video platform such as YouTube. The basic work methods of platform and video performance are reviewed in this publication.
Keywords: аналіз алгоритмів youtube; youtube